Accessibility of Island Communities to the Services of Islamic Banking Institutions in Guruapin Village, Kayoa Sub-District - Wajo, Abd. Rauf; Marasabessy, Zainal Abidin; Afandi, Namira (SAINTIS Publishing, 2024)
This study aims to analyze the accessibility of the people of Guruapin Village, Kayoa Sub-district, South Halmahera Regency, to Islamic banking services. Guruapin Village has significant economic potential in the fisheries, marine and plantation sectors, which can be the main driver of the local economy. However, this potential has not been optimally utilized due to limited access to Islamic financial services. The results show three main factors that affect the community's accessibility: the geographical distance from the Islamic bank office, the lack of banking services available in the village, and the community's low financial literacy on sharia principles. The study reveals that although the community has an awareness of the importance of Islamic banking, these constraints hinder the optimal development of the local economy. This study offers a novel integrative approach that includes the development of digital-based services, strengthening the role of agent banking, as well as sustainable financial literacy programs to improve Islamic financial inclusion. In conclusion, better access to Islamic banking services will support the development of the economic potential of Guruapin Village and improve the overall welfare of the community.